2005
DOI: 10.1074/jbc.m412212200
|View full text |Cite
|
Sign up to set email alerts
|

ADAMTS1 Proteinase Is Up-regulated in Wounded Skin and Regulates Migration of Fibroblasts and Endothelial Cells

Abstract: The metalloproteinase ADAMTS1 (a disintegrin and metalloproteinase with thrombospondin motifs) is induced under inflammatory conditions, and it is also a potent inhibitor of angiogenesis. Due to these properties, we speculated about the role of ADAMTS1 in cutaneous wound repair. Here we have shown up-regulation of ADAMTS1 expression in wounds of normal and particularly of healing-impaired genetically diabetic mice. Immunofluorescence staining identified macrophages as the source of ADAMTS1 in early wounds, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
58
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 44 publications
2
58
1
Order By: Relevance
“…TSP-1 deficiency has been found to exacerbate the pathogenesis of diabetic retinopathy (7). At high concentrations, ADAMTS-1 has been shown to inhibit the endothelial migration induced by combined treatment with VEGF and basic FGF (31). In the present study, it was found that kaempferol increased the expression of TSP-1 and ADAMTS-1 mRNA in HRECs under high glucose conditions.…”
Section: Discussionsupporting
confidence: 56%
“…TSP-1 deficiency has been found to exacerbate the pathogenesis of diabetic retinopathy (7). At high concentrations, ADAMTS-1 has been shown to inhibit the endothelial migration induced by combined treatment with VEGF and basic FGF (31). In the present study, it was found that kaempferol increased the expression of TSP-1 and ADAMTS-1 mRNA in HRECs under high glucose conditions.…”
Section: Discussionsupporting
confidence: 56%
“…Many reports have shown that hypoxia is closely related to angiogenesis. In addition, ADAMTS1 has been reported to inhibit angiogenesis in a cornea pocket assay and chorioallantoic membrane assay (35); however, Krampert et al (36) reported that ADAMTS1 has dual functions (i.e. ADAMTS1 stimulated the migration of fibroblasts at low concentrations but inhibited this process at high concentrations).…”
Section: Discussionmentioning
confidence: 99%
“…9,27,28 In vitro collagen matrices that were artificially glycated displayed a decrease in biomechanical properties when compared to nonglycated matrices both in vitro and when implanted in vivo. 29 There has also been a suggestion that collagen breakdown may be altered in the setting of diabetes due to glycation and cross linkage.…”
Section: Figure 8 Amentioning
confidence: 99%